Nonsense, common sense, and science of expert performance: Talent and individual differences - Ackerman, P. L. (Intelligence, 2013)
Controversies surrounding nature and nurture determinants of expert/elite performance have arisen many times since antiquity, and remain sources of concern in the present day. Extreme positions on this controversy are fundamentally silly — both nature and nurture are necessary determinants of expert/elite performance, but neither alone represents a sufficient causal factor. The central issues surrounding the so-called "talent myth" and the "deliberate practice theory (also referred to as the "10,000 h rule") are reviewed. Also provided is a discussion of the science of individual differences related to talent, the fundamental characteristics of talent and the role of talent in predicting individual differences in expert/elite performance. Finally, a review of the critical psychometric and statistical considerations for the prediction of individual differences in the acquisition of expert/elite performance is presented. Conclusions focus on how these various issues fit together, to provide an integrated view of the importance of talent, but also the limitations of talent identification procedures for discovering which individuals will ultimately develop expert/elite levels of performance.